Solubility limit and annealing effects on the microstructure & thermoelectric properties of Fe2V1−xTaxAl1−ySiy Heusler compounds. (15th June 2021) - Garmroudi, Fabian; Parzer, Michael; Riss, Alexander; Reumann, Nikolas; Hinterleitner, Bernhard; Tobita, Kazuki; Katsura, Yukari; Kimura, Kaoru; Mori, Takao; Bauer, Ernst
Graphical abstract: Abstract: Full-Heusler compounds with the composition Fe 2 V 1 − x Ta x Al 1 − y Si y have recently shown to exhibit some of the highest thermoelectric power factors reported so far among bulk materials due to the band convergence and band gap opening caused by the V/Ta substitution. Therefore, the solubility limit of Ta and Si regarding the stability of the L2 1 phase is investigated in this study. The crystal structure and microstructure of a large number of samples is probed by X-ray diffraction as well as scanning electron microscopy and energy dispersive X-ray analysis. The results show that the Al/Si substitution significantly hampers the solubility of Ta within the Heusler structure. Furthermore, Fe 2 V 0.9 Ta 0.1 Al and Fe 2 V 0.95 Ta 0.05 Al 0.9 Si 0.1 reveal nanoscale impurity precipitates in the microstructure, together with diffuse contrasts that indicate a non-equilibrium metastable state. For that reason, different annealing conditions, varying temperature and time, have been applied to the latter and the effect on the microstructure and thermoelectric properties is investigated. It is found that additional annealing leads to further phase segregation and grain growth of the impurity precipitates, which have a detrimental effect on the Seebeck coefficient due to their metallic-like nature. They can, however, effectively reduce the lattice thermal conductivity if their average size remains below the phonon mean free path. The thermoelectric efficiency in terms of the dimensionless figure of merit Z T is increased up to Z T = 0.3 –0.34 at 300 K which is beyond the values previously reported for Fe 2 VAl -based bulk materials.